[Recenzja]: Dmytro Blazejowskyj, Historical Šematism of the Eparchy of Peremyšl including the Apostolic Administration of Lemkivšcyna (1828-1939), L’viv 1995, ss. 1008 (...) - Prokop, Krzysztof R. (Archiwa, Biblioteki i Muzea Kościelne, 2007)
Recenzja: Dmytro Blazejowskyj, Historical Šematism of the Eparchy of Peremyšl including the Apostolic Administration of Lemkivšcyna (1828-1939), L’viv 1995, ss. 1008; Dmytro Blazejowskyj, Historical Šematism of the Eparchy of Stanislaviv from Its Establishment until the Outbreak of World War II (1885-1938), L’viv 2002, ss. 450; Dmytro Blazejowskyj, Historical Šematism of the Archeparchy of L’viv (1832-1944), vol. I – Administration and Parishes, Kyiv 2004, ss. 1004; vol. II – Clergy and Religious Congregations, Kyiv 2004, ss. 570.